Taxonomia integrativa de trematódeos da superfamília Paramphistomoidea encontrados em ruminantes abatidos na cidade de Pelotas, Rio Grande do Sul, Brasil - André Schultz Lopes (2023)
Despite the importance of livestock production to Brazil’s economy, cattle flukes are still some of the most harmful infectious agents that may affect meat, wool, milk and dairy production. Among the different trematodes that infect ruminants, the Paramphistomoidea Fischoeder, 1901 stand out for having a recognized pathogenic potential. In Brazil, despite several species being reported throughout the years, especially in the southern region, there are still several gaps when it comes to the taxonomy and biology of these helminths. Having said that, the present study aimed to identify, using an integrative approach, rumen flukes collected from slaughtered cows and sheep from the countryside of Jaguarão, Pelotas and Rio Grande, RS, between May and July of 2022. Recovered parasites were split by morphotypes, counted and fixed for morphological and molecular studies. For morphological analyses, amphistomes obtained from each city or host species were studied through different helminthologic techniques for this taxonomic group, including histological cuts, staining and mounting between glass slides and coverslips. The resulting histological cuts were observed through light microscopy, where morphological and morphometrical analyses were performed, alongside-e photographic records. Morphological identification was achieved through the use of taxonomic keys and descriptions available on previous literature. Molecular characterization evaluated parasite of different morphotypes, locations and hosts (n=11), consisting of DNA extraction, followed by PCR and sequencing of regions of the 28S rDNA nuclear gene, ITS-2 region and two regions of the cox-1 mitochondrial gene (barcode and post-barcode). Resulting sequences were compared to data available on GenBank for members of the superfamily Paramphistomoidea and utilized on phylogenetical analyses. In total, 25 rumen samples containing parasites were collected, with a total of 2969 flukes being found on the internal wall of the organs. Two morphotypes of paramphistomes were identified. The first, which was present in all rumen samples, was identified as Paramphistomum leydeni Nasmark, 1937. Morphological studies allowed the observation of diagnostic characteristics of the species, such as tegumental papillae in rows concentrated on the anterior portion of the body and terminal genitalia of the leydeni type. Molecular studies of the ITS-2 marker revealed a 100% similarity with P. leydeni isolates from Argentina, China, Turkey and Uruguay. When it comes to the cox-1 marker, the samples from Brazil diverged between 0.19-3.21% from European samples of P. leydeni, supporting the morphological identification. Beyond that, the cox-1 phylogeny revealed a well-supported branch including Chinese samples of P. leydeni, but with higher divergence values (5.47- 6.23%). The second morphotype, identified as Balanorchis anastrophus Fischoeder, 1901, was found in five rumens (20%). Morphological identification was based on diagnostic characteristics of the Balanorchiidae Stunkard, 1925, which include long, branched papillae around the oral opening, extramural faringeal sacs, terminal genitalia forming a cirrus pouch in the pre-medial portion of the body, uterus and ovary pre-testicular and genital papillae absent. Topology of the phylogenetic trees obtained and the high genetic divergences observed for different molecular markers support the separation of the Balanorchiidae from other paramphistomids of ruminants. The present study confirms the occurrence of P. leydeni in Brazil through the use of molecular studies, in addition to presenting the first molecular sequences of this species from Brazil. Furthermore, the first molecular sequences of B. anastrophus were obtained and its phylogenetic position was evaluated for the first time.